2002
DOI: 10.1542/peds.110.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Outcomes in Long-Term Survivors of Childhood Leukemia, Hodgkin’s Disease, and Non-Hodgkin’s Lymphoma: A Report From the Childhood Cancer Survivor Study

Abstract: This large, sibling-controlled, multisite study of young adult survivors of childhood leukemia, Hodgkin's disease, and non-Hodgkin's lymphoma found that survivors had significant increased risk for reporting symptoms of depression and somatic distress and that intensive chemotherapy added to this risk. However, being a cancer survivor did not compound the effects of gender and SES variables on the 2 outcomes measured. The ability of SES, gender, and treatment-related variables to predict psychological symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
256
5
10

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 331 publications
(279 citation statements)
references
References 56 publications
8
256
5
10
Order By: Relevance
“…These observations confirm the results of several previously published international studies and support the need for regular psychological/psychiatric evaluation of cancer patients and cancer survivors (13,52,53,54).…”
Section: Figuresupporting
confidence: 90%
“…These observations confirm the results of several previously published international studies and support the need for regular psychological/psychiatric evaluation of cancer patients and cancer survivors (13,52,53,54).…”
Section: Figuresupporting
confidence: 90%
“…One recent British study described marital status in nearly 10,000 childhood cancer survivors, and found a marriage formation deficit in cancer survivors relative to the general population of around 9-18% for men and around 7-10% for women, and for brain cancer in particular [7]. Preliminary analyses from the US Childhood Cancer Survivor Study, including more than 10,000 survivors, show similar tendencies [8,9], and detailed site-specific analyses on the effects of sarcomas, lymphomas, and leukemia show that cancer survivors are less likely to be married than their healthy siblings [10][11][12][13]. Marital status was only ascertained for around 60-70% of the two large childhood cohorts, and selection bias may be present.…”
Section: Introductionmentioning
confidence: 97%
“…12 Finally, in a late-effects study of psychosocial and QOL outcomes, survivors, in general, reported worse outcomes than their siblings. 15 Clearly, the current inconclusive evidence comparing children with cancer with their siblings provides little direction as to whether survivors of HSCT will be worse off than their siblings.…”
Section: Introductionmentioning
confidence: 99%